Kiler . Kiler - Machulski, Juliusz (Studio Filmowe Zebra, 1997)
Duration: 01:43:00 A spoof gangster film which was a huge commercial success in Poland. By sheer accident one morning a calm taxi driver called Jurek Kiler is arrested by the police and put in prison as a professional assassin nicknamed Kiler. Previously shy, lost and often grotesque, now Jurek is treated with awe not only by his fellow inmates, but also by the police and the prison guards as well as by women. Yet, he quickly decides to disregard this “fame” as he set free by local mafia king who wants his services. Together with a young journalist, he decides to fight the mafia and find the assassin. After numerous chases, twists and turns of action, he helps the police to arrest the real Kiler and can finally become himself. But for many people he is still a famous gangster.